Application of correlation methods for an investigation of the acoustic field in a room - ŚRODECKI, K.; ŚLIWIŃSKI, A. (Archives of Acoustics, 1991)
The aim of the present work is presenting the possibilities of applying the autocorrelation function of a room defined by Kuttruff for the estimation of some acoustic properties of rooms with various geometries. Within the work measurements tending to specify and perfect Kuttruff’s method of autocorrelation function measurement of a room were carried out. The authors focused, first of all, on the determination of the effect of frequency bandwidth of the signal used for room excitation on the autocorrelation function measured there. The work also presents the measurement results of temporal diffusion Δ – the parameter introduced by Kutruff for a quantitative estimation of autocorrelograms registered in the room. The measurements were varried out in three different rooms. The investigation prove that the autocorrelation function measurement is particularly useful in the estimation of the number and of the time distribution of strong reflections or sequences of reflections, subjectively perceived as echo, flutter echo or sound coloration. It allows also to determine the degree of sound dispersion in a room and thus it may help to estimate the quality of the reverberation decay of sound energy in the room.